If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (3)(10 + -5)(4 + -10) Combine like terms: 10 + -5 = 5 x = 3(5)(4 + -10) Combine like terms: 4 + -10 = -6 x = 3 * 5(-6) Multiply 3 * 5 x = 15 * -6 Multiply 15 * -6 x = -90 Solving x = -90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = -90
| x=(3) | | 0.3x-0.5(2x+5)=-0.8(x+4) | | (6x^2+41x+27)/(x-6) | | -6(0.1x+0.2)-1.4=-0.2 | | 0.1x-0.8(10-3x)=-0.5(x-8) | | 166-2x=250-6x | | 26.00+0.14x=22.00+0.18x | | 3log(4x)-2=10 | | X-2y-3z=9 | | 4x-10=(3x-12)2 | | -36/-9=9y | | 8x+31+4x-7=180 | | 3x-4/4-x+1/5=2x+7/10 | | 2y-44=6(y-8) | | x/0.08=5.8 | | (2x+7)(x)=99 | | (-5/4)x+(5/3)=(-1/2)x-6 | | 2x^2+-4x+-30=0 | | 4(2)= | | -5/6w+1/3=-4/9 | | -5/2+2/5u=-4/3 | | 4x+5-2x=2x-3+x | | 4x+5-2x=2x-3 | | 5/(3t-6)-2/(5t+15) | | 1x+3=14 | | 2y-8/x | | 6/5z=4/7 | | 3e^2x=1 | | (x-45)+x(x-45)+(x-45)+x=540 | | 12u^3w^2x^8+30w^8x^4= | | -11w-11=-8w | | (5v-4)(1+v)=0 |